Women’s involvement in rural development and the social welfare - Gil-Lacruz, Marta (2008)
Women are frequently situated at a risky situation at the rural social environment. Social agents aware of this situation, have to design specific programs to them in order to improve her development and participation. They have to affront not only the economical decadency of their communities but the native culture resistance to social innovation and traditional gender roles change. But in our globalize world, welfare is not possible without taking into account personal wellbeing and human and social capital importance. This article deeps into these topics and suggests possible intervention strategies.